2021
DOI: 10.3390/ma14081880
|View full text |Cite
|
Sign up to set email alerts
|

Thermosensitive Drug Delivery System SBA-15-PEI for Controlled Release of Nonsteroidal Anti-Inflammatory Drug Diclofenac Sodium Salt: A Comparative Study

Abstract: Mesoporous SBA-15 silica material was prepared by the sol–gel method and functionalized with thermosensitive polyethylenimine polymers with different molecular weight (g·mol−1): 800 (SBA-15(C)-800), 1300 (SBA-15(C)-1300) and 2000 (SBA-15(C)-2000). The nonsteroidal anti-inflammatory drug (NSAID) diclofenac sodium was selected as a model drug and encapsulated into the pores of prepared supports. Materials were characterized by the combination of infrared spectroscopy (IR), atomic force microscopy (AFM), transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The surface roughness confirmed the presence of fixed metal units on the surface. AFM was found to be a useful process to study the structural topographies of the samples. Additional comprehensive evidence was obtained by AFM observation. The AFM results confirmed that we obtained even, well-structured mesoporous films of hexagonal channels.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The surface roughness confirmed the presence of fixed metal units on the surface. AFM was found to be a useful process to study the structural topographies of the samples. Additional comprehensive evidence was obtained by AFM observation. The AFM results confirmed that we obtained even, well-structured mesoporous films of hexagonal channels.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Inflammation is a normal response of the body to various stimuli including pathogens, damaged cells, and toxic compounds and can cause different symptoms, such as pain, fever and other complications [ 42 ]. In general, in the treatment of inflammation, various drugs with anti-inflammatory or analgesic effects are administered [ 43 ]. Diclofenac sodium is a nonsteroidal, anti-inflammatory analgesic agent generally used for the treatment of pain in the joint system [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is widely recognized that diclofenac sodium belongs to non-steroidal anti-in ammatory drugs [9][10][11].…”
Section: Introductionmentioning
confidence: 99%